Nematode Management for Golf Courses in Florida - William T. Crow (EDIS, 2013)
Of all the pests that commonly affect golf course turf in Florida, nematodes are probably the least understood and most difficult to manage. Nematode problems are more common and more severe in Florida than in most other states because our climate and soils provide a perfect habitat for many of the most destructive nematode species. This 8-page fact sheet explains what plant-parasitic nematodes are, how they affect turf, how to tell if they are a problem, and how to manage them. Written by William T. Crow and published by the UF Department of Entomology and Nematology, January 2013.